2023
DOI: 10.21037/jtd-22-1469
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lysate add-on therapy in adult and childhood asthma: a systematic review and meta-analysis

Siyang Yao,
Rundong Qin,
Xiaonan Song
et al.

Abstract: Background It has been proposed that bacterial lysates may serve as a suitable immunomodulatory oral medication to improve and control asthma symptoms. However, the difference in its efficacy in adults and children remains unclear. Methods Randomized controlled trials (RCTs) evaluating OM-85 add-on therapy in asthma patients up to December 2021 were searched using PubMed, Scopus, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang database, and WP (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…They did report a second RCT on OM-85 that showed significant improvements, but for unclear reasons that study was not part of the pooled analysis. Yao et al 29 reported 22% improvement in asthma symptoms in the OM-85 groups vs. controls, but no separate data was presented in terms of intervention or placebo group. The number of asthma exacerbations during treatment was lower in the OM-85 group than in controls but with high heterogeneity (I 2 = 95%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They did report a second RCT on OM-85 that showed significant improvements, but for unclear reasons that study was not part of the pooled analysis. Yao et al 29 reported 22% improvement in asthma symptoms in the OM-85 groups vs. controls, but no separate data was presented in terms of intervention or placebo group. The number of asthma exacerbations during treatment was lower in the OM-85 group than in controls but with high heterogeneity (I 2 = 95%).…”
Section: Discussionmentioning
confidence: 99%
“…And children in the OM-85 group showed greater improvement in FEV 1 % (I 2 = 52.2%) than controls. Among those two systematic reviews 26,29 on wheezing/asthma exacerbations or asthma control, one 26 had "critical low confidence" and one 29 had "low confidence" (i.e., the review has one critical flaw and may not provide an accurate and comprehensive summary of the available studies that address the question of interest). One systematic review 30 we did not include, because not separately data exclusively on the pediatric population was presented, was done on 12 RCTs (10 RCTswere in children, accounting for 84% of participants) and showed asthma symptoms control was 22% higher and FEV1 improved more in the OM-85 group compared to controls (placebo or routine therapy, without analyze separately).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OM-85 (Broncho-Vaxom®, Broncho-Munal®, Ommunal®, Paxoral®, and Vaxoral®) is an over-the-counter oral preparation of lyophilized bacterial lysates of eight common respiratory pathogens ( H. influenzae , Diplococcus pneumoniae , Klebsiella pneumoniae , Klebsiella ozaenae , Staphylococcus aureus , S. pyogenes , Streptococcus viridans , and Neisseria catarrhalis ). OM-85 has been used for several decades in different countries (excluding the USA as OM-85 or similar products are not yet approved by the FDA) in both adults and children to treat and prevent recurrent respiratory infections, including COPD, asthma, and rhinosinusitis [ 17 , 40 ]. However, in a review in 2019, the European Medicines Agency recommended the use of BLs only for the prevention of RRTIs except for pneumonia, and they also stated that there are no adequate data to support that the BLs are effective in treating existing respiratory infections or preventing pneumonia [ 41 ].…”
Section: Successful Immunotherapeutic Bacterial Lysates For Infectiou...mentioning
confidence: 99%
“…Potential future developments in genomics and immune profiling technologies might facilitate the identification of blood-based immune signals that can be used to predict a patient's response to bacterial lysate immunotherapy under individualized treatment regimens. Subsequent investigations may concentrate on ascertaining if bacterial lysates may be used to create a tumor microenvironment that is more conducive to antitumor immune responses [ 40 , 192 , 202 ].…”
Section: Future Insightsmentioning
confidence: 99%